"Hydrous 18F-fluoroethylation" – Leaving off the azeotropic drying. (September 2017) - Kniess, Torsten; Laube, Markus; Steinbach, Jörg
Abstract: The study describes the development of a simple and effective method for 18 F-fluoroethylation -omitting the azeotropic drying step- by elution of a [ 18 F]fluoride loaded QMA column with a K2 CO3 /K222 /acetonitrile solution containing 2–3% (v/v) water directly to the 1, 2-ethylene glycol-bis-tosylate precursor. In acetonitrile containing 2–3% (v/v) water the labeling agent 2-[ 18 F]fluoroethyl tosylate ([ 18 F]FETs) was formed in 76–96% non-isolated radiochemical yield. The method was exemplified on the 18 F-fluoroethylation of three COX-2 inhibitors with different core structures. The superiority of the so called "hydrous 18 F-fluoroethylation" is characterized by a minimum loss of [ 18 F]fluoride, by fivefold increased radiochemical yield of isolated final radiotracers and by shortened overall reaction time, in comparison to conventional approach. Graphical abstract: Highlights: Design of "hydrous" acetonitrile for max. recovery of reactive [ 18 F]fluoride from SAX. Development of a facile synthesis of [ 18 F]FETs in high RCY without azeotropic drying. High yielding "hydrous 18 F-fluoro-ethylation" of COX-2 inhibitors in one-pot reaction. Fivefold increased RCY of "hydrous" compared to conventional 18 F-fluoro-ethylation.